Методичні засади оптимізації інноваційної політики асоціації підприємств за умови банківського інвестиційного кредитування - Тимашова, Л.А.; Духота, Є.В. (Економіко-математичне моделювання соціально-економічних систем, 2016)
Methodical essentials for optimization of the innovation policy for the association of manufacturing enterprises are proposed in order to reequip these enterprises technically step-by-step with the equipment for the energy saving technologies’ realization provided bank investment credits based on the use of the method of sequential analysis of variations.